Contractor's all risk insurance policy - Bangladesh General Insurance Company Ltd. (BGIC) (Brac University, 2023)
This record consists of general correspondence regarding the Contractor's All Risk (CAR) insurance policy between Brac University and BUCG for BRACU new campus project.